Numeracy Programming at Major Canadian Urban Libraries: An Exploratory Study - Budac, Andrea; Gareau-Brennan, Céline; Mucz, David; McNally, Michael B.; Rathi, Dinesh (Partnership, 2020)
The Government of Canada identifies numeracy as a foundational skill for work, learning, and life. Libraries have historically been champions of literacy; however, the role of libraries in developing numeracy skills is understudied. Specifically, there is a critical gap in studying numeracy programs offered by public libraries. This exploratory study examines the state of numeracy programming at five major urban public libraries in Canada (Calgary Public Library, Edmonton Public Library, Bibliothèques de Montréal, Ottawa Public Library, and Toronto Public Library) to understand the types and varieties of numeracy programs that they offer. The frequency of programs, the intended age range, and the program content are the main foci of this paper. The researchers examined 1166 program listings by scraping programming information from the five libraries’ websites. The data was collected for the second week of December 2015 and relied on programming descriptions from libraries' websites. Results showed that a total of 65 programs (5.6% of total programs) covered numeracy related skills. Overall, the options to learn about numeracy concepts were very limited at all of the libraries in the sample. Calgary offered the highest number of children-focused numeracy programs, while Toronto offered the greatest number of adult-focused numeracy programs. “Math/mathematics” was the most common term used to describe numeracy-related programs. This exploratory study underscores the need for greater investigation of numeracy programming in public libraries.